Securities Regulation in Thailand: Rules-based or Principles-based Approach - Vannaprathip, Ek (Journal of Roi Et Rajabhat University, 2020)
This article aims to study related problems concerning market manipulation in Thailand. The first objective is to study regulation theory and concepts of Principles-based approach and Rules-based approach that have been debating on which approach is more efficiency. And the second is to find the solutions to prevent or enforce the law in order to reach the effective securities regulation. This qualitative research study by searching and comparing the laws and regulations particularly, market manipulation in England, United State of America, Germany and Hong Kong then apply as guidelines for Thailand. This research suggests that Securities Regulation in Thailand use Rule-based approach and by itself, there are many limits in term of implementation that causes problems. Nonetheless, after studying Rules-based and Principles-based in many countries, we found ways of solutions such as applying the prudential systems of England for more corporation between the regulators and brokers, amend to sections 243/3 and clarify the keys technical terms in order to avoid confusing when enforcement is involved.